Following the Storytracks - Johnson, Greg (Journal for the Study of Religion, Nature and Culture, 2024)
Response to Sam Gill’s lead article in this issue in which the author argues why conspiracy goes too far. It cannot but be misread by all but those most sympathetic to Gill.